The Prevalence and Identification of Gastrointestinal Helminthiasis in Beef Cattle in Lamongan District - Qabilah Cita Kurnia Nastiti Soemarsono; Muridi Qomaruddin (Jurnal Ternak : Jurnal Ilmiah Fakultas Peternakan Universitas Islam Lamongan, 2021)
This study aimed to determine the prevalence and identification of gastrointestinal helminthiasis in beef cattle in Lamongan Regency. The subjects in this study were 100 cow feces divided per district as many as 20 cow feces, saturated sugar solution, PAM water, Aquadest, and 10% formalin. The stool examination was carried out using three methods as native, sedimentation, and floatation techniques. The result was positive if the analysis on the microscope shows worm eggs in beef cattle feces. The data in this study was presented in quantitative descriptive by calculating the numbers of prevalence. The results showed that the prevalence of gastrointestinal helminthiasis in beef cattle in Lamongan Regency was 24%. In Kedungpring District, it was 25%, and Paciran District was 15%, Sukodadi District was 20%, Mantup District by 20%, and Tikung District by 40%. This study concluded that the prevalence rate in Lamongan Regency was 24%. This figure tended to be high because taking the feces was done in the rainy season with high humidity, which was a factor in the high incidence of helminthiasis. Treatment of worms has not been carried out routinely by breeders, and the drums' hygiene was still not right; it was still traditional.Â